2013
DOI: 10.1158/0008-5472.can-12-2850
|View full text |Cite
|
Sign up to set email alerts
|

The Noncoding RNA MALAT1 Is a Critical Regulator of the Metastasis Phenotype of Lung Cancer Cells

Abstract: The long non-coding RNA MALAT1, also known as MALAT-1 or NEAT2, is a highly conserved nuclear ncRNA and a predictive marker for metastasis development in lung cancer. To uncover its functional importance, we developed a MALAT1 knockout model in human lung tumor cells by genomically integrating RNA destabilizing elements using Zinc Finger Nucleases. The achieved 1000-fold MALAT1 silencing provides a unique loss-of-function model. Proposed mechanisms of action include regulation of splicing or gene expression. I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
1,182
2
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,424 publications
(1,212 citation statements)
references
References 44 publications
20
1,182
2
8
Order By: Relevance
“…For example, HOTAIR has been demonstrated to be upregulated in primary breast tumours and metastases, and elevated HOTAIR expression is an indispensable predictor of eventual metastasis and death (8). MALAT-1 has been found to promote cell motility and predict poorer clinical outcome in lung cancer (9). HULC has been implicated in the regulation of hepatoma cancer cell proliferation, and higher HULC expression can be used as a non-invasive promising novel biomarker for diagnosis and/or prognosis in hepatocellular carcinoma (32,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, HOTAIR has been demonstrated to be upregulated in primary breast tumours and metastases, and elevated HOTAIR expression is an indispensable predictor of eventual metastasis and death (8). MALAT-1 has been found to promote cell motility and predict poorer clinical outcome in lung cancer (9). HULC has been implicated in the regulation of hepatoma cancer cell proliferation, and higher HULC expression can be used as a non-invasive promising novel biomarker for diagnosis and/or prognosis in hepatocellular carcinoma (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of discoveries of misregulated lncRNA expression across numerous cancer types have suggested that aberrant lncRNA expression may be a major contributor to tumourigenesis. Further, lncRNAs may add another layer to cancer research because their potential usefulness as biomarkers (8)(9)(10)(11)(12)(13)(14)(15). Therefore, to fully understand the complex mechanisms underlying carcinogenesis and cancer metastasis, the role of lncRNAs must be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we examined lncRNAs which are specifically dysregulated in 22RV1-miR-338-5p and 22RV1-miR-421 cells, gene expression profiling revealed several deregulated lncRNAs including MALAT1 which is associated with metastatic cancers (24) (Fig. 4A).…”
Section: Mir-338-5p and Mir-421 Regulate Oncogenic Long Non-coding Rnmentioning
confidence: 99%
“…32 One study identified a set of genes that might act to promote lung cancer metastasis, reporting that the expression of these genes depends on MALAT1. [34][35][36][37] These MALAT1 target genes were either associated with metastasis or represented critical regulators of metastasis establishment, and were strongly reduced by the loss of MALAT1. 34 These reports support the hypothesis that MALAT1 is an activator of metastasis and affects metastatic processes.…”
Section: Malat1-prc1 Pathwaymentioning
confidence: 99%